Importance of genotype for risk stratification in arrhythmogenic right ventricular cardiomyopathy using the 2019 ARVC risk calculator . (29th June 2022) - Protonotarios, Alexandros; Bariani, Riccardo; Cappelletto, Chiara; Pavlou, Menelaos; García-García, Alba; Cipriani, Alberto; Protonotarios, Ioannis; Rivas, Adrian; Wittenberg, Regitze; Graziosi, Maddalena; Xylouri, Zafeirenia; Larrañaga-Moreira, José M; et al.
Abstract: Aims: To study the impact of genotype on the performance of the 2019 risk model for arrhythmogenic right ventricular cardiomyopathy (ARVC). Methods and results: The study cohort comprised 554 patients with a definite diagnosis of ARVC and no history of sustained ventricular arrhythmia (VA). During a median follow-up of 6.0 (3.1, 12.5) years, 100 patients (18%) experienced the primary VA outcome (sustained ventricular tachycardia, appropriate implantable cardioverter defibrillator intervention, aborted sudden cardiac arrest, or sudden cardiac death) corresponding to an annual event rate of 2.6% [95% confidence interval (CI) 1.9–3.3]. Risk estimates for VA using the 2019 ARVC risk model showed reasonable discriminative ability but with overestimation of risk. The ARVC risk model was compared in four gene groups: PKP2 ( n  = 118, 21%); desmoplakin ( DSP ) ( n  = 79, 14%); other desmosomal ( n  = 59, 11%); and gene elusive ( n  = 160, 29%). Discrimination and calibration were highest for PKP2 and lowest for the gene-elusive group. Univariable analyses revealed the variable performance of individual clinical risk markers in the different gene groups, e.g. right ventricular dimensions and systolic function are significant risk markers in PKP2 but not in DSP patients and the opposite is true for left ventricular systolic function. Conclusion: The 2019 ARVC risk model performs reasonably well in gene-positive ARVC (particularly for PKP2 ) but is more limited in gene-elusive patients. Genotype should be included in future risk models for ARVC. Structured Graphical Abstract: Structured Graphical Abstract ARVC, arrhythmogenic right ventricular cardiomyopathy; AUC, area under the curve; ECHO, echocardiography; CMR, cardiac magnetic resonance; HR, hazard ratio; LGE, late gadolinium enhancement; LV, left ventricular; LVEDD, left ventricular enddiastolic diameter; LVEF, left ventricular ejection fraction; PLAX, parasternal long-axis; PVC, premature ventricular complex; RV, right ventricular; RVEDV, right ventricular end-diastolic volume; RVEF, right ventricular ejection fraction; RVOT, right ventricular outflow tract; TWI, T-wave inversion; VT, ventricular tachycardia.